THE INFLUENCE OF INTELLECTUAL CAPITAL AND PROFIT MANAGEMENT ON STOCK RETURNS - Arya Manda; Murtanto (ZILLZELL MEDIA PRIMA, 2024)
This study aims to determine the effect of intellectual capital and earnings management on stock returns with dividend policy as a moderating variable. This research is motivated by the importance of information about the factors that affect stock returns. The population of this study were mining companies listed on the Indonesia Stock Exchange in 2020 – 2022. The sample of this study was 23 issuers or 69 company financial statement data used in this study. This study uses multiple linear regression and moderate regression analysis. The results of this study are that intellectual capital has no effect on stock returns, and earnings management has a positive effect on stock returns.